Posttraumatic Stress Disorder: A Theoretical Model of the Hyperarousal Subtype - Weston, Charles S. (Frontiers in Psychiatry, 2014)
Posttraumatic stress disorder (PTSD) is a frequent and distressing mental disorder, about which much remains to be learned. It is a heterogeneous disorder; the hyperarousal subtype (about 70% of occurrences and simply termed PTSD in this paper) is the topic of this article, but the dissociative subtype (about 30% of occurrences and likely involving quite different brain mechanisms) is outside its scope. A theoretical model is presented that integrates neuroscience data on diverse brain regions known to be involved in PTSD, and extensive psychiatric findings on the disorder. Specifically, the amygdala is a multifunctional brain region that is crucial to PTSD, and processes peritraumatic hyperarousal on grounded cognition principles to produce hyperarousal symptoms. Amygdala activity also modulates hippocampal function, which is supported by a large body of evidence, and likewise amygdala activity modulates several brainstem regions, visual cortex, rostral anterior cingulate cortex (rACC), and medial orbitofrontal cortex (mOFC), to produce diverse startle, visual, memory, numbing, anger, and recklessness symptoms. Additional brain regions process other aspects of peritraumatic responses to produce further symptoms. These contentions are supported by neuroimaging, neuropsychological, neuroanatomical, physiological, cognitive, and behavioral evidence. Collectively, the model offers an account of how responses at the time of trauma are transformed into an extensive array of the 20 PTSD symptoms that are specified in the Diagnostic and Statistical Manual of Mental Disorders, 5th edition. It elucidates the neural mechanisms of a specific form of psychopathology, and accords with the Research Domain Criteria framework